Efektivitas Discovery Learning pada Pembelajaran Geografi untuk mengurangi Miskonsepsi Peserta Didik - Indriana, Ayu; Yusuf, Muhammad; Maru, Rosmini; Saputro, Alief (UNIVERSITAS NEGERI MAKASSAR, 2021)
This study aims to: 1) find out how the picture of learning outcomes of students by using the Discovery The purpose of this study was to determine the application of the Discovery Learning learning model and the effect of the Discovery Learning learning model in overcoming the misconception of atmospheric material. Data was collected in February-March 2020. The research design method used was an experimental method with the Pretest and Posttest control group design. In this study conducted in two classes, namely X IPS1 as an experimental class and X IPS2 in SMA Negeri 2 Makassar as a control class. The instrument used is a multiple-choice diagnostic test with the CRI (Certainity Response Index) method. The results of the study that there is an influence of student learning models regarding learning models, it can be concluded that the concept of atmospheric component components decreased misconception by 34%, the concept of weather and climate components decreased misconception by 33% and the concept of climate classification components experienced a decrease in misconception by 32%. It can be concluded that there is an influence of Discovery Learning learning model in overcoming misconceptions that occur in atmospheric material in SMA Negeri 2 Makassar.